Analysis of Under Frequency Load Shedding System - Rajagukguk, Antonius; Ervianto, Edy; Firdaus, Firdaus; Dika, Rian (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2024)
Load shedding is a protection scheme to maintain the stability of the electric power system. When there is an imbalance between the power generated and the load power, load shedding will release the load to restore power balance. This research aims to design and analyze the load shedding system at Private Company to see whether it is running well and meets the PRC-006-5 standard regarding the frequency operating limit, which must be in the range of 49.42 Hz to 50.58 Hz. The method that will be used in this research is to carry out testing with software and then analyze the power and frequency response due to the generator being removed from the system. The testing mechanism that will be carried out is to simulate the effect of a lack of power for the load supply on the load shedding system. From the research results, it is known that the existing load shedding scheme needs to be evaluated. Evaluation is carried out on steps 1 and 2, so that the load shedding limit for step 1 becomes 49.5 Hz and the pickup time for step 4 becomes 400 ms.